The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1177/1759720x211025894
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulation with IL-17 and TNF-α in spondyloarthritis: focus on the eye and the central nervous system

Abstract: Tumor necrosis factor alpha (TNF-α) and interleukin-17 (IL-17) are two pro-inflammatory cytokines involved in the pathophysiology of spondyloarthritis (SpA). Therapies targeting TNF-α or IL-17 are used as a second line among SpA patients failing non-steroidal anti-inflammatory drugs. The choice of such treatment has to take into account the patient’s comorbidities. Neurologic diseases are common and their association with SpA deserves to be studied. Therefore, the role of TNF-α and IL-17 cytokines is worth inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 149 publications
0
5
0
Order By: Relevance
“…The underlying pathophysiology of axSpA is thought to be driven by inflammation, which results in systemic and local bone loss and local new bone formation ( 33 ). Inflammation in this pathology is mediated by pro-inflammatory cytokines, such as IL6, TNF-α, and IL17 ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The underlying pathophysiology of axSpA is thought to be driven by inflammation, which results in systemic and local bone loss and local new bone formation ( 33 ). Inflammation in this pathology is mediated by pro-inflammatory cytokines, such as IL6, TNF-α, and IL17 ( 34 , 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we found that MLT inhibited the activation of the NF-κB pathway in TNF-α-induced inflammatory HaCaT cell, and MLT remarkably decreased the expression of NF-κB downstream genes, IL-1α and IL-1β , in LL37- or TNF-α-treated HaCaT cells. Moreover, TNF-α and IL-17A were also reported as the key cytokines in AD and rosacea ( 32 , 64 , 65 ). Here, we also noted the repression of MLT on IL-17A/TNF-α in rosacea-like mice.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that serum cytokine measurements can be employed as indicators of the severity of illness. Actually, cytokines such as IL-8, IL-17, and TNF- α have been shown to serve as biomarkers alongside variuos implications in other diseases [ [40] , [41] , [42] ].…”
Section: Basic Components Of Autoimmunity During Auto13mentioning
confidence: 99%